2019
DOI: 10.1111/jam.14270
|View full text |Cite
|
Sign up to set email alerts
|

Applications and limitations of regulatoryRNAelements in synthetic biology and biotechnology

Abstract: Summary Synthetic biology requires the design and implementation of novel enzymes, genetic circuits or even entire cells, which can be controlled by the user. RNA‐based regulatory elements have many important functional properties in this regard, such as their modular nature and their ability to respond to specific external stimuli. These properties have led to the widespread exploration of their use as gene regulation devices in synthetic biology. In this review, we focus on two major types of RNA elements: r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 142 publications
0
21
0
Order By: Relevance
“…The activities of riboregulators are often mediated by interaction of the nascent transcript with small molecules, ribosomes, tRNAs, or regulatory proteins. As such, riboregulators are potential therapeutic targets, and may provide synthetic biology applications [52][53][54][55]. Since conditional premature transcription termination regulates biofilm formation, virulence, and expression of antibiotic resistance genes in other bacteria [40,51,56,57], efforts to identify and characterize genes likely to be controlled by riboregulators in P. aeruginosa would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…The activities of riboregulators are often mediated by interaction of the nascent transcript with small molecules, ribosomes, tRNAs, or regulatory proteins. As such, riboregulators are potential therapeutic targets, and may provide synthetic biology applications [52][53][54][55]. Since conditional premature transcription termination regulates biofilm formation, virulence, and expression of antibiotic resistance genes in other bacteria [40,51,56,57], efforts to identify and characterize genes likely to be controlled by riboregulators in P. aeruginosa would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression can also be regulated post-transcriptionally. Riboswitches are regulatory mRNA elements in the 5′ untranslated region that are capable of regulating gene expression through small molecule-induced structural switching [214]. They add a layer of regulation, but are less explored for the engineering of non-model microbes relative to model organisms like E. coli.…”
Section: Regulated Gene Expressionmentioning
confidence: 99%
“…In this mechanism, mRNA forms two distinct shapes depending on the presence of a specific small molecule, which either blocks or allows translation. Examples of the use of riboswitches for engineering of non-model microbes include theophylline for inducible production of biofuels and other compounds [215], lysine to balance flux for competing pathways [214,216], and flavonoids such as naringenin for increased production of flavonoids [217]. Recently, thermophilic riboswitches have also been identified and used to regulate biofuel production [218].…”
Section: Regulated Gene Expressionmentioning
confidence: 99%
“…A large number of studies have shown that ncRNAs are widely involved in the regulation of bacterial oxidative stress resistance [ 4 , 5 ], biofilm formation [ 6 , 7 , 8 ], osmotic pressure [ 9 , 10 ], virulence factor expression [ 11 , 12 ], bacterial antibiotic resistance [ 13 , 14 , 15 ], and many other physiological processes, among which the research of ncRNAs on the regulation of antibiotic resistance has become an important issue in recent years due to global drug resistance emergence. In view of their regulatory flexibility and low metabolic burden, ncRNAs have become one of the most versatile biobricks in the field of synthetic biology and metabolic engineering [ 16 , 17 , 18 ]. According to a number of studies, bacterial ncRNAs play regulatory roles in different modes, the most widely known of which are functioning via the interaction with the target mRNA [ 5 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%